2022
DOI: 10.1007/s11356-022-21079-z
|View full text |Cite
|
Sign up to set email alerts
|

Stainless steel catalyst for air pollution control: structure, properties, and activity

Abstract: With the awakening of environmental awareness, the importance of air quality to human health and the proper functioning of social mechanisms is becoming increasingly prominent. The low cost and high efficiency of catalytic technique makes it a natural choice for achieving deep air purification. Stainless steel alloys have demonstrated their full potential for application in a variety of catalytic fields. The diversity of 3D networks or fibrous structures increases the turbulence within the heterogeneous cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 162 publications
(204 reference statements)
0
3
0
Order By: Relevance
“…Additionally, it can differentiate between different isotopes of the same element, making it valuable for isotopic labeling applications (Helaluddin et al 2016 ; Korn et al 2007 ; Todolí 2019 ; Woods and Fryer 2007 ). This technique is widely used for detecting metallic pollutants in complex environmental samples (Cregut et al 2022 ) and the presence of trace metals on synthesized materials (Li et al 2022 ; Wang et al 2022 ). Although some studies have explored the elemental composition of biodiesel (Amais et al 2012 ; de Souza et al 2011 ; Elkadi et al 2014 ; Ghisi et al 2011 ; Lepri et al 2011 ; Pereira et al 2014 ; Pillay et al 2012 ; Sánchez et al 2015 , 2014 ; Woods and Fryer 2007 ), very few studies have looked at the elemental composition of biodiesels and their oil feedstock together (Chaves et al 2011 ; Lepri et al 2011 ), and no study has reported the effect of thermal stress on the distribution of metallic and non-metallic elements from oil to biodiesel and biogylcerol phases produced from it.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it can differentiate between different isotopes of the same element, making it valuable for isotopic labeling applications (Helaluddin et al 2016 ; Korn et al 2007 ; Todolí 2019 ; Woods and Fryer 2007 ). This technique is widely used for detecting metallic pollutants in complex environmental samples (Cregut et al 2022 ) and the presence of trace metals on synthesized materials (Li et al 2022 ; Wang et al 2022 ). Although some studies have explored the elemental composition of biodiesel (Amais et al 2012 ; de Souza et al 2011 ; Elkadi et al 2014 ; Ghisi et al 2011 ; Lepri et al 2011 ; Pereira et al 2014 ; Pillay et al 2012 ; Sánchez et al 2015 , 2014 ; Woods and Fryer 2007 ), very few studies have looked at the elemental composition of biodiesels and their oil feedstock together (Chaves et al 2011 ; Lepri et al 2011 ), and no study has reported the effect of thermal stress on the distribution of metallic and non-metallic elements from oil to biodiesel and biogylcerol phases produced from it.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is indispensable to develop the in situ growth technology of Cu–Mn–O catalysts on a low-cost substrate with good mechanical strength, high thermal conductivity, and excellent oxidation resistance. Nevertheless, there are few works focusing on this aspect. …”
Section: Introductionmentioning
confidence: 99%
“…Fluidized bed reactors provide the best gas-solid body contact; therefore, their dimensions can be smaller than those of packed or monolythic bed reactors. However, this requires using catalysts with high mechanical strength, because during fluidization, abrasion of the catalyst bed may occur [37,59,60].…”
mentioning
confidence: 99%